FORMULATION AND IN VITRO EVALUATION OF IMMEDIATE RELEASE TABLETS OF ANTIPSYCHOTIC DRUG RISPERIDONE (International Journal of Food and Nutritional Sciences, 2023)
Risperidone is a novel antipsychotic with dopaminergic and serotonergic effects. The main pharmacological activities of risperidone include serotonin 5-HT2 receptor blockade and dopamine D2 antagonism. The main objective of this research is to develop various formulations of immediate release tablet of risperidone to increase solubility and bioavailability by using various Superdisintegrants such as Sodium Starch Glycolate, Croscarmellose and Crospovidone, by wet granulation method. The drug-excipients compatibility was determined by using UV and DSC thermogram. The powder blend and tablets of risperidone were evaluated for various pre and post compression parameters like physiochemical parameters, angle of repose, compressibility index, hausner’s ratio, tablet hardness, friability, content uniformity and in vitro disintegration and dissolution studies and their results were found to be satisfactory. Outcomes of study indicates that maximum in vitro dissolution profile of formulation F6 were found to have equivalent percentage of drug release and concluded that F6 is better and similar to innovator product.